1997
DOI: 10.1046/j.1365-2265.1997.800904.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the 5α‐reductase Type 2 gene in eight Mexican patients from six different pedigrees with 5α‐reductase‐2 deficiency

Abstract: The presence of the same mutation in 4 patients from 3 families indicates the increased prevalence of this mutation in a particular ethnic group, suggesting a common ancestry for the gene defect in these patients. The existence of hot spots is supported by the mutations in codons 34 and 207 which have also been found in other ethnic groups. Interestingly, the patient who presented 2 different mutations, one of them previously undescribed, was reared as a male and exhibited a more masculine phenotype. Further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 15 publications
3
31
0
2
Order By: Relevance
“…The SRD5A2 gene analyses revealed four different mutations in 6 patients, all of which have earlier been reported as pathologic [11,12,13,14]. Patients 1 and 2 were sisters, and showed a homozygous deletion of thymine at nucleotide position c.655 of exon 4 (c.655delT).…”
Section: Resultsmentioning
confidence: 95%
“…The SRD5A2 gene analyses revealed four different mutations in 6 patients, all of which have earlier been reported as pathologic [11,12,13,14]. Patients 1 and 2 were sisters, and showed a homozygous deletion of thymine at nucleotide position c.655 of exon 4 (c.655delT).…”
Section: Resultsmentioning
confidence: 95%
“…Ser and Gly115 ? Asp, have been found predominantly in subjects from Latin American countries such as Brazil, Mexico, and Dominican Republic (Thigpen et al 1992a;Cai et al 1996;Canto et al 1997). Similarly, the Gly85 ?…”
Section: Discussionmentioning
confidence: 95%
“…Their father was healthy and was the carrier of L224H. Canto et al 16 reported a patient with penoscrotal hypospadias, who carried G203S and G115D, and studies indicated that the activity of SRD5A2 and the synthesis of DHT decreased in cultured genital skin fibroblasts carrying these mutations. In this study, some heterozygous mutations in SRD5A2 were also found in five patients, healthy parents (Table 3) and controls.…”
Section: Discussionmentioning
confidence: 99%